Empty - Weyn, Suzanne (Scholastic Press, 2010)
When, just ten years in the future, oil supplies run out and global warming leads to devastating storms, senior high school classmates Tom, Niki, Gwen, Hector, and Brock realize that the world as they know it is ending and lead the way to a more environmentally-friendly society.